MiR-4319 targets tuftelin 1 to reduce malignancy of cervical cancer cells: MiR-4319 tuftelin 1 in CC - Zheng, Lijun; Ren, Qiongzhen; Zhu, Weipei; Tao, Xiaomin; Guo, Liangsheng (Cellular and Molecular Biology, 2024)
Cervical cancer (CC) is the most common malignant tumor of female reproductive system. MiR-4319 has been identified as an anti-oncogene in various cancers. In the present study, role of miR-4319 in CC was identified. Colony formation, flow cytometer, wound healing, and transwell assays were used to detect CC cell proliferation, apoptosis, migration, and invasion. The expression of miR-4319 was decreased in clinical CC tissues and CC cell lines. Upregulation of miR-4319 suppressed cell viability, proliferation, migration, and invasion, and induced cell apoptosis in CC cells. Moreover, tuftelin 1 (TUFT1) was verified as a direct target of miR-4319, as confirmed by dual-luciferase reporter assay. Additionally, TUFT1 expression was remarkably increased in clinical CC tissues and CC cell lines and was negatively associated with miR-4319 expression. Furthermore, overexpression of TUFT1 partially restored the effects of miR-4319 mimic on cell viability, proliferation, migration, invasion, and cell apoptosis in CC cells. To conclude, miR-4319 played an anti-cancer role in the occurrence and development of CC, which might be achieved by targeting TUFT1.